Ocular Surface Squamous Neoplasia – An Update on Diagnostic Modalities and Management - Parul Jain; Aastha Singh; Avilasha Mohapatra; Ritu Arora; Gahan A Reddy (Delhi Journal of Ophthalmology)
Ocular surface squamous neoplasia (OSSN) encompasses a group of squamous neoplasms of conjunctival and corneal epithelium such as conjunctival intraepithelial neoplasia, corneal epithelial dysplasia and squamous cell carcinoma. Patients with OSSN present with decreased visual acuity, irritation in the eye, and an ocular surface lesion with varied clinical morphologies, associated prominent feeder vessels, and often a keratin plaque. While the definitive diagnosis of OSSN is histopathological, imaging modalities such as optical coherence tomography (OCT), OCT-angiography, and ultrasound biomicroscopy are noninvasive techniques to identify the disease, its extent and monitor progression. Surgical excision with wide tumor-free margins has been traditionally employed to manage the condition. However, with promising results obtained with medical modalities such as chemotherapy and immunomodulatory agents, there has been a paradigm shift in managing patients with OSSN. This review describes in detail clinical features, latest diagnostic modalities, and management guidelines for OSSN.